KONTRIBUSI PENDAPATAN ASLI DAERAH KABUPATEN BANTAENG DALAM PEMBANGUNAN INFRASTRUKTUR - Anas, Surya Dewan Perdana; Mustarin, Basyirah; Aisyah, Nur (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
Local revenue is the right of local governments that is recognized as an increase in the value of net worth obtained from local taxes, and local levies, The results of segregated regional wealth management and other legitimate sources are intended to support fiscal decentralization and regional development. This type of research is qualitative research with a normative syar'i approach and an empirical juridical approach. The results of this study show that the contribution of Regional Original Income (PAD) of Bantaeng Regency between 2019-2020 in financing infrastructure development is still relatively small because it only ranges from 4-5% when compared to direct expenditure allocations.